The budget impact of patterned frequency-modulated oral stimulation to promote non-nutritive sucking in preterm infants in the United States - Muench, Tobias; Fernández Barceló, Carla; Veloz, Alex; Saunders, Rhodri (Frontiers in Pediatrics, 2025)
BackgroundPremature childbirth interrupts in-utero development of essential functionalities including non-nutritive sucking (NNS), a pre-requisite for full oral feeding (FOF), often a requirement for hospital discharge. Patterned and frequency-modulated oro-somatosensory stimulation (PFOS) can help preterm infants develop NNS. This study assessed the health-economic impact of PFOS in preterm infants in the United States (US).MethodsA budget impact analysis modeled the hospital care pathway for preterm infants through a decision tree and Markov model with a 5-year time horizon. The analysis examined 100 hypothetical preterm infants with gestational age at birth (GAB) 25–30 weeks, using PFOS (NTrainer™) or standard of care (SoC). Input data were taken from published literature. Key outcomes were total costs, neonatal intensive care unit (NICU) days, infections, and rehospitalizations. Probabilistic and one-way sensitivity analyses were performed to address uncertainty.ResultsFor 100 preterm infants, insurance payer costs were estimated at $21,713,932 and $24,063,242 for PFOS and SoC, respectively. On average, costs with PFOS were lower by $2,349,309 (95% uncertainty interval (UI): −$342,130; $4,945,657). Sensitivity analysis showed that PFOS was cost saving in 96% of simulations. Results were driven by reduced time to FOF and discharge (−577 NICU days), while decreasing infections and rehospitalizations. From the hospital perspective, the model resulted in total costs of $8,746,157 with PFOS and $9,736,209 with SoC, a difference of $990,051 (95% UI: -$163,528; $2,093,355). Introducing PFOS was cost saving for hospitals in 96% of the simulations according to the model estimates.ConclusionPFOS is expected to reduce the cost of care associated with developing NNS in preterm infants in the US from both a payer and hospital perspective, being especially cost-effective in older preterm infants (GAB 29–30).